Clausal-Internal Switching in Urdu-English: An Evaluation of the Matrix Language Frame Model - Ali, Asad; Jabbar, Qaisar; Malik, Nazir Ahmad; Kiani, Humayun Baber; Noreen, Zumra; Toan, Ly Ngoc (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
The core of this paper is to employ the Matrix Language Frame (MLF) model on Urdu-English clausal-internal switching to identify whether the Matrix Language Frame model potentially accounts for the bilingual linguistic competence efficiently. For this, a qualitative methodology has been adopted for this study. For empirical evidence, data has been taken from eighty Urdu- English bilinguals within a naturalistic setting after categorizing them into four groups, and each group has 20 participants. After conducting audio-recording through non-participant interviews in an informal setting, the collected data was transcribed. The MLF model posited that two languages are fused in a single Intra-CP of a mixed string. The linearly dominant language is Matrix language (ML) that incorporates only late outsider system morphemes. Odd is Embedded language (EL) that supplies content morphemes satisfying the system morpheme principle (SMP) uniformly and morpheme order principle (MOP). The present study ubiquitously scrutinizes that naturalistic data of Urdu-English bilinguals highlights the innovative results: it predicts that Matrix language (ML) is unidentified in intra-CP, no late outsider system morphemes linearize a code-switched sentence, unparalleled constituent and clausal structure, System Morpheme Principle (SMP) and Morpheme Order Principle (SMP) provides the illegitimate output and computes ungrammatical sentences hence; the Matrix Language Frame model redundantly and inconsistently accounts for Urdu-English naturalistic data and its principles have failed to compute Urdu-English naturalistic data.